Abscisic acid-mediated modifications in water transport continuum are involved in cadmium hyperaccumulation in Sedum alfredii. (April 2021) - Tao, Qi; Jupa, Radek; Dong, Qin; Yang, Xin; Liu, Yuankun; Li, Bing; Yuan, Shu; Yin, Junjie; Xu, Qiang; Li, Tingqiang; Wang, Changquan
Abstract: Abscisic acid (ABA) play a crucial role in plant acclimation to heavy-metals stresses. Nevertheless, the effects of ABA on long-distance transport and its consequences for cadmium (Cd) accumulation are insufficiently understood. Here, we investigated the effects of ABA on the development of the whole-plant water transport pathway and implications for Cd uptake and transport to the shoot of Sedum alfredii . Exposure to Cd stimulated the production of endogenous ABA levels in the non-hyperaccumulating ecotype (NHE), but not in the hyperaccumulating ecotype (HE). Increased ABA levels in NHE significantly reduced aquaporin expressions in roots, the number of xylem vessel in stem, dimensions and densities of stomata in leaves, but induced leaf osmotic adjustment. Furthermore, the ABA-driven modifications in NHE plants showed typically higher sensitivity to ABA content in leaves compared to HE, illustrating ecotype-specific responses to ABA level. In NHE, the ABA-mediated modifications primarily affected the xylem transport of Cd ions and, at the cost of considerable water delivery limitations, significantly reduced delivery of Cd ions to shoots. In contrast, maintenance of low ABA levels in HE failed to t limit transpiration rates and maximized Cd accumulation in shoots. Our results demonstrated that ABA regulates Cd hyperaccumulation of S. alfredii through specific modifications in the water transport continuum. Highlights: Differences in ABA synthesis drive ability of S. alfredii to accumulate Cd. Cd induced different ABA production in different ecotype of S. alfredii. ABA regulates development of the whole plant water transport pathway of S. alfredii . Elevated ABA level hindered Cd accumulation via impaired water status in NHE. Maintenance of minimum ABA level promoted uptake and delivery of water and Cd in HE.